A Reactive Superhydrophobic Platform for Living Photolithography (Adv. Mater. 36/2022). Issue 36 (8th September 2022) - Xie, Xinjian; Chen, Xinghao; Levkin, Pavel A.; Feng, Wenqian
Abstract : Superhydrophobic Surfaces Researchers have designed a new type of superhydrophobic surfaces with chemical reactivity. In article number 2203619, Wenqian Feng and co‐workers demonstrate living photolithography on such superhydrophobic surfaces to graft functional moieties with controlled the densities and species. The distinctive properties of this surface can provide new insight into intelligent superhydrophobic material development and practical applications, such as aqueous/oil microdroplet arrays, multi‐anti‐counterfeiting labels, and integrated microfluidic reactors with enzymes for chemical logic learning.